Direct manipulation of malaria parasites with optical tweezers reveals distinct functions of plasmodium surface proteins - Hegge, Stephan; Uhrig, Kai; Streichfuss, Martin; Kynast-Wolf, Gisela; Matuschewski, Kai; Spatz, Joachim P.; Frischknecht, Friedrich (ACS nano, 2012)
Plasmodium sporozoite motility is essential for establishing malaria infections. It depends on initial adhesion to a substrate as well as the continuous turnover of discrete adhesion sites. Adhesion and motility are mediated by a dynamic actin cytoskeleton and surface proteins. The mode of adhesion formation and the integration of adhesion forces into fast and continuous forward locomotion remain largely unknown. Here, we use optical tweezers to directly trap individual parasites and probe adhesion formation. We find that sporozoites lacking the surface proteins TRAP and S6 display distinct defects in initial adhesion; trap(-) sporozoites adhere preferentially with their front end, while s6(-) sporozoites show no such preference. The cohesive strength of the initial adhesion site is differently affected by actin filament depolymerization at distinct adhesion sites along the parasite for trap(-) and s6(-) sporozoites. These spatial differences between TRAP and S6 in their functional interaction with actin filaments show that these proteins have nonredundant roles during adhesion and motility. We suggest that complex protein-protein interactions and signaling events govern the regulation of parasite gliding at different sites along the parasite. Investigating how these events are coordinated will be essential for our understanding of sporozoite gliding motility, which is crucial for malaria infection. Laser tweezers will be a valuable part of the toolset.
Gesehen am 06.04.2018